ADAPTING COMMUNICATION IN MULTICULTURAL CLASSROOMS: EVIDENCE FROM INDONESIAN PRE-SERVICE TEACHERS IN AUSTRALIA - Dwinova Sabriena Unique; Fahrur Rozi (Universitas HKBP Nommensen, 2026)
The increasing diversity of students in global education has transformed classrooms into multicultural environments that demand adaptive and effective communication. In such contexts, teachers are required not only to deliver content but also to navigate linguistic and cultural differences that may influence classroom interaction. This study examines the communication strategies used by Indonesian pre-service teachers during their teaching practicum in multicultural classrooms in Australia. A qualitative case study approach was employed involving five pre-service teachers. Data were collected through interviews, observations, and documentation, and analyzed inductively to identify patterns of communication practices and challenges. The findings indicate that effective communication strategies include understanding student characteristics through systematic observation, utilizing adaptive instructional media, adjusting learning objectives to students’ abilities, and applying flexible teaching roles. Major challenges identified include language barriers, diverse student behavior, and mismatched learning pace. These challenges were addressed through multimodal communication strategies such as gestures, visual aids, and interactive classroom management techniques. This study highlights the importance of adaptive and culturally responsive communication in supporting effective teaching and learning in multicultural classroom settings.